2016
DOI: 10.1016/j.celrep.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic and Dynamic Changes in Alternative Splicing during Induction of Pluripotency Are Coordinated by Numerous RNA-Binding Proteins

Abstract: SUMMARY Alternative splicing (AS) plays a critical role in cell fate transitions, development, and disease. Recent studies have shown that AS also influences pluripotency and somatic cell reprogramming. We profiled transcriptome-wide AS changes that occur during reprogramming of fibroblasts to pluripotency. This analysis revealed distinct phases of AS, including a splicing program that is unique to transgene-independent induced pluripotent stem cells (iPSCs). Changes in the expression of AS factors Zcchc24, Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 29 publications
(41 reference statements)
7
100
0
Order By: Relevance
“…We therefore analysed gene expression during the reprogramming of mouse fibroblasts into iPSCs via OCT4/SOX2/KLF4/MYC from two independent studies (Chen et al, 2016; Cieply et al, 2016). Specifically, we examined genes that required OCT4 for their expression in ESCs (OCT4-dependent) and separated these into genes associated with BRG1-independent or BRG1-dependent OCT4 binding at neighbouring distal regulatory elements in ESCs (see Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore analysed gene expression during the reprogramming of mouse fibroblasts into iPSCs via OCT4/SOX2/KLF4/MYC from two independent studies (Chen et al, 2016; Cieply et al, 2016). Specifically, we examined genes that required OCT4 for their expression in ESCs (OCT4-dependent) and separated these into genes associated with BRG1-independent or BRG1-dependent OCT4 binding at neighbouring distal regulatory elements in ESCs (see Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the pre-existing chromatin state at a subset of OCT4 target sites (BRG1-independent) may allow them to be activated more rapidly. Importantly, these observations suggest that chromatin structure likely plays an important role in regulating how OCT4 engages with and functions in the genome not only in mouse ESCs but also during reprogramming and development.
10.7554/eLife.22631.017Figure 6.BRG1-dependency reveals distinct modes of OCT4 function of distal regulatory elements during reprogramming and development.( A ) A time course of gene expression changes (log2 fold change) during OKSM-mediated reprogramming of mouse embryonic fibroblasts to iPSCs (Chen et al, 2016; Cieply et al, 2016). The expression changes of OCT4-dependent genes neighbouring the 20% of distal OCT4 targets that were most dependent upon BRG1 for normal OCT4 binding (BRG1-dependent) or the 20% of distal OCT4 targets that were least dependent (BRG1-independent) following BRG1 removal were quantified and visualised as a smoothed trendline ±95% confidence interval.
…”
Section: Resultsmentioning
confidence: 99%
“…CELF2, another RBP that was significantly induced during myofibroblastic differentiation of HSC, has been strongly linked to EMT in other types of stem-like cells, including those involved in hepatocarcinogenesis [24]. Conversely, RBM47, an RBP that was profoundly suppressed in MF-HSC relative to Q-HSC, has been shown to promote mesenchymal-to-epithelial transitions (MET) in pluripotent stem cells derived from mouse embryonic fibroblasts [7,25]. Therefore, our subsequent studies in HSC and injured livers focused on IGF2BP3, CELF2 and RBM47.…”
Section: Rbps Are Differentially Expressed In Quiescent and Myofibrobmentioning
confidence: 99%
“…However, Igf2bp3 is merely one of several RBPs that have been shown to regulate epithelial-to-mesenchymal transitions (EMT) and mesenchymal-to-epithelial transitions (MET) during development and carcinogenesis. Indeed, we discovered that Celf2 and Rbm47, two other RBPs that have been reported to reciprocally regulate EMT/MET in stem-like cells [7,24], are also differentially regulated as HSC become MF. Although relatively little is known about the RBP interactome that controls these complex fate decisions in any cell type, we found that knocking down Igf2bp3 also suppressed accumulation of Celf2 in HSC.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…We illustrate these parts of the Procedure by analyzing a published time course of reprogramming to pluripotency using a doxycycline-inducible system in murine cells 23 and the directed differentiation of human induced pluripotent stem cells (iPSC) to hippocampal dentate gyrus granule neurons 24 . We have provided FASTQ files, a metadata table, as well as pre-processed query data so that the user can walk through all of these steps.…”
Section: Experimental Designmentioning
confidence: 99%